Kinin and Purine Signaling Contributes to Neuroblastoma Metastasis - Ulrich, Henning; Ratajczak, Mariusz Z.; Schneider, Gabriela; Adinolfi, Elena; Orioli, Elisa; Ferrazoli, Enéas G.; Glaser, Talita; Corrêa-Velloso, Juliana; Martins, Poliana C. M.; Coutinho, Fernanda; Santos, Ana P. J.; Pillat, Micheli M.; et al. (Frontiers in Pharmacology, 2018)
Bone marrow metastasis occurs in approximately 350,000 patients that annually die in the U.S. alone. In view of the importance of tumor cell migration into the bone marrow, we have here investigated effects of various concentrations of stromal cell-derived factor-1 (SDF-1), bradykinin- and ATP on bone marrow metastasis. We show for first time that bradykinin augmented chemotactic responsiveness of neuroblastoma cells to SDF-1 and ATP concentrations, encountered under physiological conditions. Bradykinin upregulated VEGF expression, increased metalloproteinase activity and induced adhesion of neuroblastoma cells. Bradykinin augmented SDF-1-induced intracellular Ca2+ mobilization as well as resensitization and expression of ATP-sensing P2X7 receptors. Bradykinin treatment resulted in higher gene expression levels of the truncated P2X7B receptor compared to those of the P2X7A full-length isoform. Bradykinin as pro-metastatic factor induced tumor proliferation that was significantly decreased by P2X7 receptor antagonists; however, the peptide did not enhance cell death nor P2X7A receptor-related pore activity, promoting neuroblastoma growth. Furthermore, immunodeficient nude/nude mice transplanted with bradykinin-pretreated neuroblastoma cells revealed significantly higher metastasis rates compared to animals injected with untreated cells. In contrast, animals receiving Brilliant Blue G, a P2X7 receptor antagonist, did not show any specific dissemination of neuroblastoma cells to the bone marrow and liver, and metastasis rates were drastically reduced. Our data suggests correlated actions of kinins and purines in neuroblastoma dissemination, providing novel avenues for clinic research in preventing metastasis.